PENGGUNAAN CONGKLAK UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN MOTIVASI BELAJAR SISWA KELAS 2 PADA TOPIK PERKALIAN - Reni Adriana; Niko Sudibjo (Akademika : Jurnal Teknologi Pendidikan, 2017)
The purpose of this research is to analyze the improvement of conceptualunderstanding and motivation to learn of students of class 2 SD using traditional gamescongklak as learning media. This classroom action research was implemented in threecycles. The participants were six students of grade 2. The data were collected throughobservations, interviews, photos, tests, and rubrics. This study suggests that using congklakis effective in improving the student’sconceptualunderstanding and motivation to learn inlearning multiplication